An Overview of Local Positioning System: Technologies, Techniques and Applications - Sahib Hasan, Hameedah; Hussein, Mohamed; Mad Saad, Shaharil; Azuwan Mat Dzahir, Mohd (International Journal of Engineering and Technology, 2018)
Positioning system like global position system (GPS) and Local position system (LPS) have become very important in a large number of applications such as monitoring and tracking, etc. Because of the limitations of GPS in indoor environments due to the lack of line of sight (LoS), the use of LPS has become a true necessary to estimate userâ€™s or object position with a good accuracy. In order to choose the best LPS system, a compromise between accuracy, precision, power consumption, coverage and cost should be taken into account. This paper introduces an overview of LPS performance parameters, current technologies, techniques and methods used by LPS. On the other hand, the comparison between LPS technologies and techniques used based on those technologies are also discussed. Furthermore, the LPSâ€™s applications that have been done by previous researches such as human tracking, object tracking, animal tracking and automatic guide vehicle (AGV) tracking will be discussed. We believe this paper would catalyze further investigation by the researcher which is interested on the LPS field.Â